Towards a market based composite political risk indicator for country oil and gas industry sectors - Simpson, John (Centre for Research in Applied Economics, Curtin Business School, 2009)
The purpose of this paper is to test an international oil and gas market model, hypothesised to arrive at new indicator of pure composite political risk for country oil and gas sectors. Current political risk ratings are largely subjectively quantified and are not frequently published. Investors in oil and gas industry portfolios as well as trade and investment policy formulators should be interested that there is a strong theoretical and practical basis where pure political risk indicators may be obtained daily rather than monthly using stock market generated data. A systemic international capital asset pricing model is a useful framework as long as available financial and economic information is captured along with systemic interdependence and control introduced for country size and wealth effects. If so, an indication of the influence of human (political) factors in each country oil and gas industry sector can be provided.